THE EFFECT OF TRANSFORMATIONAL LEADERSHIP, MOTIVATION FOR ACHIEVEMENT, AND JOB SATISFACTION ON CIVIL SERVANTS’ INNOVATION BEHAVIOR IN THE MERAUKE REGENCY GOVERNMENT - Trio Rendra Yustiono; Meinarni Asnawi; Sandra Sukmaning Adji (Transpublika Publisher, 2024)
The Merauke Regency Government has a mandate to continue to improve public service innovation. However, budget limitations, the availability of supporting infrastructure, and the lack of skilled human resources are the main obstacles in implementing innovation behavior within the Merauke Regency Government. According to the literature, several factors affect innovation behavior in an organization. This study seeks to analyze the influence of transformational leadership style, motivation for achievement, and job satisfaction on innovation behavior in civil servants within the Merauke Regency Government. With data from 114 civil servants in the Merauke Regency Government processed with SEM-PLS, this study found that transformational leadership and job satisfaction had a positive and significant effect on the innovation behavior of civil servants in the Merauke Regency Government, while motivation for achievement had no significant effect. Based on these results, the proposed policy recommendations are to increase transformational leadership and job satisfaction within the Merauke Regency government.